2006
DOI: 10.1093/jn/136.4.981
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Bing Sweet Cherries Lowers Circulating Concentrations of Inflammation Markers in Healthy Men and Women ,

Abstract: The purpose of this study was to determine the effects of consuming sweet cherries on plasma lipids and markers of inflammation in healthy humans. Healthy men and women (n = 18) supplemented their diets with Bing sweet cherries (280 g/d) for 28 d. After a 12-h fast, blood samples were taken before the start of cherry consumption (study d 0 and 7), 14 and 28 d after the start of cherry supplementation (study d 21 and 35), and 28 d after the discontinuation (study d 64) of cherry consumption. After cherries were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 41 publications
8
131
2
3
Order By: Relevance
“…Moreover, when 18 healthy male and female adults (age 45-61) consumed 280 g of Bing sweet cherries daily, a , and densitometry analysis (bottom) of the immunoreactive bands normalized to β-actin, with results represented as mean ± SEM; n = 7/group. Asterisk indicates statistically significant difference between the groups (p < 0.05) comparable amount of cherry (approximately 4 g/kg/ day) as in this study, they showed a significant drop in serum C-reactive protein (hsCRP) levels compared to placebo controls (Kelley et al 2006). These findings support the idea that cherry polyphenols have antiinflammatory properties.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, when 18 healthy male and female adults (age 45-61) consumed 280 g of Bing sweet cherries daily, a , and densitometry analysis (bottom) of the immunoreactive bands normalized to β-actin, with results represented as mean ± SEM; n = 7/group. Asterisk indicates statistically significant difference between the groups (p < 0.05) comparable amount of cherry (approximately 4 g/kg/ day) as in this study, they showed a significant drop in serum C-reactive protein (hsCRP) levels compared to placebo controls (Kelley et al 2006). These findings support the idea that cherry polyphenols have antiinflammatory properties.…”
Section: Discussionsupporting
confidence: 86%
“…A 2 % (w/w) Montmorency tart cherry dose was chosen based on previous studies in humans (Kelley et al 2006), as well as those conducted in our laboratory demonstrating the beneficial effects of phytochemical-rich berry fruits (i.e., blueberry, strawberry, cranberry, blackberry, black currant, and boysenberry) on cognition, motor function, and suppression of inflammation and oxidative stress in aged animals and accelerated aging models (Casadesus et al 2004;Goyarzu et al 2004;Shukitt-Hale et al 2005;Galli et al 2006;Shukitt-Hale et al 2007, 2009aMalin et al 2011). The amount of ground corn was adjusted in the control diet to compensate for the added volume of the freeze-dried cherry powder, in accordance with established methodology (ShukittHale et al 1998;Youdim et al 2000).…”
Section: Dietmentioning
confidence: 99%
“…These have been identified in natural foods from black tea to tart cherries to fish oil. Antioxidant and anti-inflammatory agents have been identified in tart cherries, and a study among healthy, non-exercising individuals demonstrated that sweet cherry consumption decreased serum inflammatory biomarkers (Kelley, Rasooly, Jacob, Kader, & Mackey, 2006). This has led to speculation that consumption of tart cherries may be effective in alleviating symptoms in inflammatory conditions (Tall et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on this issue were randomized trials with very specific exposures, such as highpressurized orange juice (Sanchez-Moreno et al, 2003), carotenoid-rich vegetables and fruits (Watzl et al, 2005), sweet cherries (Kelley et al, 2006), berries and apples (Freese et al, 2004) and vegetable soup 'gazpacho' (Sanchez-Moreno et al, 2004), and provided non-conclusive results, as most of them found decreased inflammatory levels with the intake of these food items, but one failed to show a reduction of CRP after several weeks of intervention (Freese et al, 2004). All of the observational studies reported an inverse association between fruit and vegetable intake and inflammatory markers (Esmaillzadeh et al, 2006), mainly in the elderly (Gao et al, 2004, Wannamethee et al, 2006, but none have examined the effect of fruits separately from vegetables, in men and women of all ages from the same population.…”
Section: Introductionmentioning
confidence: 99%